The effects of recreational demand characteristics on space preference in urban forests - KARAGÖZOĞLU, CENGİZ (ISTANBUL UNIV-CERRAHAPASA, 2019)
Natural areas are important in meeting the needs of people in recreation. While these areas are planned, care should be taken to create a sustainable space to protect the natural environment and meet the needs of visitors. It is also important to observe visitors to provide quality recreation facilities that meet the needs and demands of visitors while protecting nature. The types of functional areas used by visitors, the kinds of routes preferred by reaching these areas, the most or least visited places, and the kinds of activities preferred by different groups to determine the flow and density of the area provide the necessary information to plan these areas in a better way. Knowing this preference makes it easier to meet the demand of visitors. In the present study, the spatial distribution of visitors in Kocaeli Urban Forest was investigated to reveal the flow of visitors. The effect on the spatial distribution of road attributes with spatial features has been revealed. Furthermore, the relationship between the visit and the spatial distribution characteristics was analyzed. Finally, the study was revised completely, and suggestions were made about the urban forest.
Keywords: Recreation; spatial behavior; spatial distribution; urban forest; visitor flow